The Model of Voronoi’s Polygons and Density: Diagnosis of Spatial Distribution of Education Services of EJA in Divinópolis, Minas Gerais, Brazil. - De Castro Guadalupe, Diogo; Mourão Moura, Ana Clara (TeMA - Journal of Land Use, Mobility and Environment, 2014)
This paper represents the application of a methodology that supports urban environmental studies to the identification and mapping of areas of influential points or spatial phenomenal occurrences, using the techniques of Multicriterial Analysis and of Voronoi Polygon. It focuses on the use of institutional alphanumeric database transformed into spatial analysis by the use of GIS and models of distribution, to support decision-making regarding allocation strategies and expansion of centers of experimental education called “EJA” (Youth and Adults Education) in Divinópolis, a city in the state of Minas Gerais, Brazil. It describes the process of data that composes information which makes possible to perform urban analyzes and to simulate the scenarios considering the expansion of the system and the review of the allocation of some points.